2011
DOI: 10.1590/s0103-84782011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de grãos de arroz irrigado colhidos com diferentes graus de umidade em função da aplicação de fungicida

Abstract: O objetivo do trabalho foi verificar o efeito de fungicida aplicado na parte aérea das plantas, na quantidade de grãos inteiros de cultivares de arroz irrigado colhidos com diferentes graus de umidade. O experimento foi conduzido durante o ano agrícola de 2007/08 e 2008/09, em delineamento experimental de blocos ao acaso em esquema fatorial, com cultivo em faixas (4x4x6) e quatro repetições. O fator principal, em faixas, foi composto por quatro cultivares de arroz irrigado: 'BR-IRGA 409', 'IRGA 417', 'IRGA 422… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(5 reference statements)
1
2
0
1
Order By: Relevance
“…Therefore, the variation in the percentage of whole and broken grains between the different genotypes studied in the two agricultural years corroborates the results of Canellas et al (1997). Teló et al (2011) evaluated different lowland rice cultivars and found that the percentage of whole grains ranged from 63% to 65% under ideal harvesting conditions. In our sample, the percentages of whole grains in the sprinkler irrigation depth at 150% of ETc in 2011/2012 and in all sprinkler irrigation depths in 2014/2015 were similar to those found by Teló et al (2011) (61.59% and 58.97%, respectively), demonstrating that grain quality in this irrigation system was similar to that of flood irrigation.…”
Section: Resultssupporting
confidence: 80%
“…Therefore, the variation in the percentage of whole and broken grains between the different genotypes studied in the two agricultural years corroborates the results of Canellas et al (1997). Teló et al (2011) evaluated different lowland rice cultivars and found that the percentage of whole grains ranged from 63% to 65% under ideal harvesting conditions. In our sample, the percentages of whole grains in the sprinkler irrigation depth at 150% of ETc in 2011/2012 and in all sprinkler irrigation depths in 2014/2015 were similar to those found by Teló et al (2011) (61.59% and 58.97%, respectively), demonstrating that grain quality in this irrigation system was similar to that of flood irrigation.…”
Section: Resultssupporting
confidence: 80%
“…Milling yield was considered the percentage of milled and polished rice obtained by weighing the grains after processing 100 g rice with husk (Brasil, 2009); using a ricetesting machine to test rice samples. The percentage of whole grains was calculated according to the method described in Teló et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that works on the effects of the association between N, Si, and fungicide applications on the industrial quality of irrigated rice grains are still scarce. Some studies have related grain quality to factors such as different humidity levels and fungicide use (Teló et al, 2011), irrigation suppression (Londero et al, 2015), high temperature (Nakata et al, 2017), and shading (Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos demonstram que o rendimento de grãos inteiros é uma importante característica de determinação da qualidade do arroz, valores elevados de grãos inteiros conferem maior valor comercial o produto (Odek, 2017;Teló et al, 2011). Neste estudo o elevado rendimento de grãos pode estar relacionado com a obtenção de grãos integrais, ou seja, não houve a etapa de polimento.…”
Section: Perfil Colorimétricounclassified